To use the Distributive Property, we will distribute each term in the first expression to each term in the second expression:
\((3x - 5)(2x + 2)\)
We will use the distributive property as follows:
-
Distribute \(3x\) to both terms in \((2x + 2)\):
\[ 3x \cdot 2x = 6x^2 \] \[ 3x \cdot 2 = 6x \]
-
Distribute \(-5\) to both terms in \((2x + 2)\):
\[ -5 \cdot 2x = -10x \] \[ -5 \cdot 2 = -10 \]
Now we can combine all the results:
\[ 6x^2 + 6x - 10x - 10 \]
Now combine like terms:
\[ 6x^2 + (6x - 10x) - 10 = 6x^2 - 4x - 10 \]
Thus, the expression rewritten using the Distributive Property is:
\[ 6x^2 - 4x - 10 \]
So the correct response is:
6x² - 4x - 10